Antifungal activities and active ingredients of Melodinus suaveolens Champ. ex Benth. Issue 12 (18th June 2018) - Xu, Yanan; Ling, Siquan; Zeng, Dongqiang; Tang, Wenwei
Abstract: Four Melodinus species with antifungal activity were found in survey of the floral resources, in Shiwan Mountain Natural Reserve, Guangxi Province, China. Crude methanolic extracts of the twigs and leaves of Melodinus suaveolens exhibited potent antifungal activities against the plant pathogenic fungi Colletotrichum musae, Colletotrichum graminicola, Colletotrichum gloeosporioides and Alternaria musae, and the ethyl acetate fraction inhibited these pathogens at rates of 85.37, 91.47, 72.77 and 89.87%, respectively (5 mg/mL). A new compound, (2 R, 3 S, 5 S, 6 R )-1- O -methyl- chiro -inositol was isolated from the ethyl acetate fraction, along with 15 known compounds. The antifungal activities of compounds (1 –16 ) were evaluated for the first time. Compound (4 ) had potent antifungal activity against C. gloeosporioides, C. graminicola and A. musae. Abstract :